Implications of Third Culture Kids (TCK)'s Socio-Cultural Background on Language Identity - An Exploration - Ilyani Abd Khalid (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
The Third Culture Kid (TCK); is the term used to describe individuals whose formative years are spent outside their origin’s culture. A TCK is defined as an individual whose sense of belonging is not specified to any particular culture for their self-definition. This paper will be looking at the effects of English learning as the second (L2) and/or foreign (FL) language on the establishment of language and cultural identity in Third Culture Kid (TCK). The target group selected in this paper is specifically the TCKs from non-native English speaking background. The aspects to be explored are the impact of L2/FL on native language (L1) in general, and then delving deeper into the effects of English as the L2/FL on the TCKs’ L1 specifically. The paper will also be discussing the process of language identity formation in the TCKs with respect to English learning, the construction of these students’ cultural identity, and the role of teachers as cultural mediators in the classroom for this particular cohort. The theoretical framework for the analysis on the cultural aspect will be using the Hofstede’s Cultural Dimensions structure as a reference. Keywords: Third Culture Kid (TCK), L2, identity, socio-cultural